You are on page 1of 3

Tangents to a curve

Basically, if y = f(x) then the tangent line at the point (x1, f(x1)) is given by:

y f(x1) = f(x1) (x x1)


If we let f(x1) = y1, then we get:

y y1 = f(x1) (x x1)

Here, f(x1) is the gradient of the tangent at x1. It can be found by finding the first derivative of f(x) and then substituting x1 into the resulting equation to give a number value. f(x) relates the change in the gradient along the curve with respect to x. (Note: the gradient of the tangent at any point on a graph is also the gradient of the graph at that point, and the instantaneous rate of change of the variable at that point.) To find the tangent line: If given the gradient (i.e. what f(x1) equals) and f(x): Note: may be given f(x1) in the question if it says the tangent is parallel to the x-axis (gradient = 0) or a given linear equation (in this case the given linear equation y = mx+c will have the same gradient as the tangent, so f(x1) = m), tangent is perpendicular to a line (f(x1) = -1/m), or tangent is a turning point of the curve (gradient = 0), etc. [x1] find the general equation for f(x), and find x1 by subbing the given f(x1) value into that equation [y1] find y1 by substituting x1 into f(x) [tangent equation] Sub y1, x1, and f(x1) into [y f(x1) = f(x1) (x x1)] Note: tangents gradient may be represented in the general equation by mT. The normal equation is similar to the tangents general equation by has a different gradient (mN

1) 2) 3)

= (1/mT):

y y1 = mN(x x1) = (1/mT)(x x1)


1) 2) 3) If given either x1 or y1, and f(x): [y1 or x1] find the other y1 or x1 value by subbing the given x1 or y1 into f(x) [f(x1)] find f(x), then find the gradient of the tangent at the point by subbing x1 into f(x) [tangent equation] Sub y1, x1, and f(x1) into [y f(x1) = f(x1) (x x1)]

Q12.
x3-3x2, coordinates where tangent a) // to x-axis b) // to y-3x+2 a) Let f(x) = x3 3x2 f(x) = 3x2 6x If the tangent is parallel to the x-axis, its angle must equal 0, i.e. f(x) = 0 f(x) = 3x2 6x = 0 x(3x 6) = 0 x=0 f(0) = 03 3(0)2 = 0 (0,0) Or: 3x 6 = 0 x = 2 f(2) = 23 3(2)2 = 4 (2, 4)

x3 3x2 has a tangent parallel to the x-axis at (0,0) and (2, 4). b) If the tangent is parallel to y = 3x + 2, they must share the same gradient, i.e. f(x) = 3 f(x) = 3x2 6x = 3 3x2 6x + 3 = 0 x2 2x + 1 = 0 (x 1)2 = 0

1|P a g e

x=1 f(1) = 13 3(1)2 = 2 (1, 2)

x3 3x2 has a tangent parallel to y = 3x + 2 at (1, 2).

Q13.
a) x2+4x-1, eqn of tangent with gradient 6 b) eqn of normal @ point a) Let f(x) = x2 + 4x 1 f(x) = 2x + 4 If the tangent has a gradient of 6, f(x) = 6 2x + 4 = 6 x=1 f(1) = (1)2 + 4(1) 1 = 4 So, x2 + 4x 1 has a tangent with gradient 6 at (1,4). The eqn of the tangent is given by: y y1 = mT(x x1) y 4 = 6(x 1) y = 6x 2 The equation of the tangent with gradient 6 for x2 + 4x 1 is y = 6x 2 b) The eqn of the normal at point (1,4) is given by: y y1 = mN(x x1) = (1/mT)(x x1) y 4 = (1/6)(x 1) y = (-1/6)x + 25/6 or: x + 6y = 25 y1 = 4, x1 = 1, mT = 6 y1 = 4, x1 = 1, mT = 6

The equation of the normal at the point where the tangent has a gradient 6 for x2 + 4x 1 is x + 6y = 25

Q14.
y=2x2-2x+5, eqn of normal @ point where curve crosses y-axis Let f(x) = 2x2 2x + 5 Point where curve crosses y-axis is when x=0. Sub x=0 into eqn y = 2x2 2x + 5 to get: y = 2(0)2 2(0) + 5 = 5 Gradient of tangent at that point, (0,5) is given by f(0), where: mT = f(x) = 4x 2 f(0) = 4(0) 2 = 2 Thus, the eqn of the normal at point (0,5) is given by: y y1 = mN(x x1) = (1/mT)(x x1) y 5 = (1/2)(x 0) y = x +5 The equation of the normal at the point where y = 2x2 2x + 5 crosses the y-axis is y = x +5. y1 = 5, x1 = 0, mT = 2

Q15.
y=x2+4x, eqn of normal @ x=2, x=1 Let f(x) = x2 + 4x f'(x) = 2x + 4

2|P a g e

At x = 2: f(2) = (2)2 + 4(2) = 4 f(2) = 2(2) + 4 = 0 the eqn of the tangent at point (2,4) is given by: y y1 = mT(x x1) y 4 = 0(x 4) y=4 This tangent line is parallel to the x-axis. The normal is perpendicular to this so its eqn at (2,4) must be x = 2 At x = 1: f(1) = (1)2 + 4(1) = 3 f(1) = 2(1) + 4 = 2 the eqn of the normal at point (1,3) is given by: y y1 = mN(x x1) = (1/mT)(x x1) y (3) = (1/2)(x 1) y = x + 7/2 The equation of the normal for y = x2 + 4x is x = 2 when x = 2, and y = x + 7/2 when x = 1. y1 = 3, x1 = 1, mT = f(1) = 2 y1 = 4, x1 = 2, mT = f(2) = 0

Q16.
y=x3+2x2-3x+1, eqn of normal @ x=2 Let f(x) = x3 + 2x2 3x + 1 f'(x) = 3x2 + 4x 3 f(2) = (2)3 + 2(2)2 3(2) + 1 = 7 f(2) = 3(2)2 + 4(2) 3 = 1 Thus, the eqn of the normal at point (2,7) is given by: y y1 = mN(x x1) = (1/mT)(x x1) y 7 = (1/1)(x (2)) y = x +5 The equation of the normal at the point for y = x3 + 2x2 3x + 1 when x=2 is y = x +5. y1 = 7, x1 = 2, mT = f(2) = 1

Hope that helped you understand, Sabi. :) - Annie

3|P a g e